THE CORRELATION BETWEEN TEST TAKING STRATEGIES AND READING COMPREHENSION SCORE IN READING TEST (RETAIN, 2020)
Abstract In order to succeed in reading comprehension test, the learners should choose the most appropriate strategy dealing with reading test. Moreover, by using the suitable strategy while completing reading test, it is believed that it will help the learners to accomplish the test easily. The purpose of this quantitative study was to find out the correlation between test taking strategies and reading comprehension scores in reading test. Another aim of this study was examining the kind of test taking strategies utilized by EFL learners in accomplishing reading test. The data of this study were gained through online questionnaire toward 90 participants of junior and senior university students in one of University in Surabaya. The result showed that the EFL learners mostly utilized metacognitive strategies (mean score 3.68) than cognitive strategies (mean score 3.59) while completing reading comprehension test. The result also revealed that test taking strategies and reading comprehension scores was positively correlated. The significance level of correlation was r = 0.251, and it was categorized as low correlation. Keywords: test taking strategies, reading comprehension test, reading comprehension score.